Compiling a harmonized database from Germany's 1978 to 2003 sample surveys of income and expenditure - Timm Bönke; Carsten Schröder; Clive Werdt (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
We outline a procedure for combining six cross-sections of the German Sample Survey of Income and Expenditure, and discuss potential pitfalls of such a venture. Particularly, we investigate the consequences of a major break in the survey design for inter-temporal comparisons of expenditure categories: a reduction of the surveying period from twelve to three month taking place between the census years 1993 and 1998. We demonstrate that for several commodities a division-by-four of annually-surveyed expenses cannot guarantee inter-temporal comparability of expenditure distributions. We suggest and test the performance of several alternative conversion procedures. Suitability of conversion strategies hinges upon good-specific purchase properties.
Keywords: C8; D1; D3; I3; 330; German Sample Survey of Income and Expenditure; annual vs. trimestrial data; Haushaltsbudget-Statistik; Zeit; Stichprobenverfahren; Deutschland